2012
DOI: 10.1007/s10047-012-0632-x
|View full text |Cite
|
Sign up to set email alerts
|

Left heart bypass support with the Rotaflow Centrifugal Pump® as a bridge to decision and recovery in an adult

Abstract: Since left heart bypass or biventricular circulatory assist with an extracorporeal centrifugal pump as a bridge to decision or recovery sometimes requires long-time support, the long-term durability of extracorporeal centrifugal pumps is crucial. The Rotaflow Centrifugal Pump(®) (MAQUET Cardiopulmonary AG, Hirrlingen, Germany) is one of the centrifugal pumps available for long-term use in Japan. However, there have been few reports of left heart bypass or biventricular circulatory support over the mid-term. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Rota ow ® ) can bridge over a longer time period to a permanent device in unclear conditions. In the literature one case with a bridge to recovery is reported, in our case it was a bridge-to-bridge concept [15]. The most frequent complications are bleeding, thromboembolism and vascular complications, followed by neurological and respiratory problems [3].…”
Section: Discussionmentioning
confidence: 65%
“…Rota ow ® ) can bridge over a longer time period to a permanent device in unclear conditions. In the literature one case with a bridge to recovery is reported, in our case it was a bridge-to-bridge concept [15]. The most frequent complications are bleeding, thromboembolism and vascular complications, followed by neurological and respiratory problems [3].…”
Section: Discussionmentioning
confidence: 65%
“…Kashiwa et al [15] reported a case in which left heart bypass support with the Rotaflow centrifugal pump was performed as a bridge to transplantation decision and recovery. Of note, the pump could be used continuously for more than 30 days [15]. In the present study, e-VAD was used as a bridge to transplantation in a 72-year-old female patient for 48 days.…”
Section: Kjtcvsmentioning
confidence: 99%
“…Biomaterials contribute widely to the development of human therapeutics ( 1 3 ). Metals, in particular, are broadly useful in many fields due to their hardness, strength, durability, and workability.…”
Section: Introductionmentioning
confidence: 99%